2019
DOI: 10.1016/j.marenvres.2019.104757
|View full text |Cite
|
Sign up to set email alerts
|

Show your beaks and we tell you what you eat: Different ecology in sympatric Antarctic benthic octopods under a climate change context

Abstract: Sympatry can lead to higher competition under climate change and other environmental pressures, including in South Georgia, Antarctica, where the two most common octopod species, Adelieledone polymorpha and Pareledone turqueti, occur side by side. Since cephalopods are typically elusive animals, the ecology of both species is poorly known. As beaks of cephalopods are recurrently found in top predator's stomachs, we studied the feeding ecology of both octopods through the evaluation of niche overlapping and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Data regarding Hg concentrations in Antarctic octopods is still scarce (Matias et al, 2019) as previous studies mainly focused on squid species and analysed few tissues (Anderson et al, 2009;Cipro et al, 2018;Seco et al, 2020;Xavier et al, 2016). However, both A. polymorpha and P. turqueti had higher T-Hg concentrations relative to the data on T-Hg levels in Antarctic squids from previous studies (Table 3).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Data regarding Hg concentrations in Antarctic octopods is still scarce (Matias et al, 2019) as previous studies mainly focused on squid species and analysed few tissues (Anderson et al, 2009;Cipro et al, 2018;Seco et al, 2020;Xavier et al, 2016). However, both A. polymorpha and P. turqueti had higher T-Hg concentrations relative to the data on T-Hg levels in Antarctic squids from previous studies (Table 3).…”
Section: Discussionmentioning
confidence: 75%
“…The reason for that is beaks are capable of absorbing and creating strong links with Hg due to its high specificity for amino groups present in proteins (Barriada et al, 2008), with Hg varying greatly as differences in beak pigmentation reflect different protein content (Miserez et al, 2008). Similarly to nitrogen stable isotope signatures accompany the gradual formation of the beaks (Cherel & Hobson, 2005;Chouvelon et al, 2011), it was also found recently that Hg increases from the rostrum towards the crest which is the most recent and metabolically active region of the beak (Queirós et al, 2020) Within Antarctic cephalopods, the octopod species Adelieledone polymorpha (Robson, 1930) and Pareledone turqueti (Joubin, 1905) are good bioindicators of the health of South Georgia's benthic ecosystems, as both species are short-lived and the most abundant cephalopod benthic species in the region (Barratt et al, 2008;Collins et al, 2004;Matias et al, 2019). These two species occupy the same habitat throughout their lifecycle (i.e.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations